2006
DOI: 10.1111/j.1529-8817.2006.00161.x
|View full text |Cite
|
Sign up to set email alerts
|

MOLECULAR PHYLOGENY OF SELECTED MEMBERS OF THE ORDER THALASSIOSIRALES (BACILLARIOPHYTA) AND EVOLUTION OF THE FULTOPORTULA1

Abstract: Recent phylogenetic studies of the diatoms indicate that members of the order Thalassiosirales occupy an interesting position in the diatom evolutionary tree. Despite their radial morphology and scaly auxospores, they are consistently recovered in molecular analyses as a member of subdivision Bacillariophytina and a sister clade to non-fultoportulate and non-radial lithodesmioids. This study included 46 species from nine traditionally accepted extant genera, and analyzed 43 nuclear small subunit (SSU) rRNA seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
181
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(191 citation statements)
references
References 48 publications
8
181
1
Order By: Relevance
“…the Lithodesmiales and the Thalassiosirales. However, such discoveries prompt new and more detailed structural and cytological investigations to reveal whether the differences are more apparent than real and to understand their basis (Kaczmarska et al 2006). We still are lacking much detail about the life cycle and protoplast structure in many diatom genera, so that some of the sister relationships recovered in the molecular analyses remain 'bald' cladistic hypotheses, with little biological meaning.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…the Lithodesmiales and the Thalassiosirales. However, such discoveries prompt new and more detailed structural and cytological investigations to reveal whether the differences are more apparent than real and to understand their basis (Kaczmarska et al 2006). We still are lacking much detail about the life cycle and protoplast structure in many diatom genera, so that some of the sister relationships recovered in the molecular analyses remain 'bald' cladistic hypotheses, with little biological meaning.…”
Section: Discussionmentioning
confidence: 99%
“…This fact led Medlin et al (1993) and Medlin & Kaczmarska (2004) to suggest that the central strutted process could be homologous with the bilabiate process of the Lithodesmiales. Kaczmarska et al (2006) have suggested further that the external tubes of the marginal strutted processes could be formed by a fragmentation, then encircling and fusing of the marginal fringe in the Lithodesmiales to form hollow tubes above the pore structure of the fultoportula. Two different types of strutted processes are known in the Thalassiosirales (Kaczmarska et al 2006), but they could all be derived in this fashion.…”
Section: The Thalassiosiralesmentioning
confidence: 99%
See 2 more Smart Citations
“…The genus Hyalodiscus contrast clearly to the more derived genus Coscinodiscus which has two types of rimoportulae instead of one and a more complex structure of loculi (large and small ones). Both more primitive families Hyalodiscaceae and Coscinodiscaceae are differentiated from the more advanced Thalassioraceae by missing of fultoportulae (KaczMaRSKa et al 2006). In spite of the generally different frustule geometry of Hyalodiscus (short pervalvar axis) and Podosira (extended pervalvar axis) ultrastructural similarities are given especially in the type of rimoportulae (labiate processes), but their densities differ considerably (much less dense in Hyalodiscus than Podosira see Round et al 1990).…”
Section: Discussionmentioning
confidence: 94%